Hemoglobina Köln diagnosticada em programa de triagem neonatal em São José do Rio Preto, SP - Schiaveto, Emanuele C. [UNESP]; Vidotto, Alessandra [UNESP]; Siqueira, Fátima A.M. [UNESP]; Naoum, Paulo C. [UNESP]; Fett-Conte, Agnes C.; Bonini-Domingos, Claudia R. [UNESP] (My University, 2002)
Hemoglobinopathies are a diverse group of inherited recessive disorders that include thalassemias and sickle cell disease. They were the first genetic diseases to be characterized at the molecular level and consequently have been used repeatedly as a prototype for the development of new techniques of mutation detection. A major group of the structural hemoglobins exhibit the property of instability in solution, resulting from their altered molecular structures. Mutation of amino acids in the globin affects the structure of the molecule turning it unstable and they are classified as unstable hemoglobins. Due to the great diversity of the mutation points, substitutions and deletions of amino acids, the unstable forms are very varied. Hemoglobin Köln is the unstable variant most described in literature and the third discovered in Brazil, the others are Hb Niterói and Hb Hasharon. Moderate anemia, jaundice and the presence of dark urine characterize Hb Köln's clinical manifestations. In a neonatal screening program we identified a child suspected of having hemoglobin Köln, which was confirmed by electrophoretic procedures and HPLC. Evaluations by different laboratory examinations and the family study aided in a precocious diagnosis, thereby facilitating to minimize the current symptoms of the abnormal hemoglobin, and thus the family received support with genetic and educational counseling of these hereditary alterations.
Köln Hemoglobin found in Neonatal Screening Program in São José do Rio Preto, São Paulo, Brazil
Keywords: Köln hemoglobin; Neonatal screening; Unstable hemoglobins